Analisis Pengaruh Knowledge Sharing Dalam Penerapan Sistem Manajemen Mutu Iso 9001:2008 Terhadap Kinerja Inovasi Dan Kinerja Karyawan - Fajar Maulana; R Andi Sularso; Purnamie Titisari (Jurnal Manajemen dan Kewirausahaan, 2018)
Recently, the sugar industry is facing a very tight market competition. This condition encourages companies to improve quality and competitiveness immediately through improvement of  customer satisfaction consistently and continuously. The purpose of this research is to examine and discuss the effect of knowledge sharing in applying ISO 9001:2008 Quality Management System to the performance of employees innovation and performance at Jatiroto Sugar Factory. Data obtained through questionnaires as 130 respondents with proportional stratified random sampling. Data analysis uses The Structural Equation Modelling (SEM). The result of the research shows a significant influence between : 1) knowledge sharing on the implementation of ISO 9001:2008; 2) knowledge sharing on innovation performance, 3) knowledge sharing on employee performance, 4) implementation of ISO 9001:2008 on innovation performance, and 5) implementation of ISO 9001:2008 on employee performance. The indirect effect was found a significant in knowledge sharing on innovation performance through the application of ISO 9001:2008. However, there is no influence of knowledge sharing on employee performance through the application of ISO 9001:2008. https://doi.org/10.26905/jmdk.v6i1.2045